Modern health-seeking behaviour and associated factors among mothers having under 5-years old children in Shire town, Tigray, Ethiopia: A cross-sectional study 2018 - Girmay T. Weldesamuel; Tsega T. Alemayoh; Hagos T. Atalay; Teklewoini M. Zemichael (AOSIS, 2019)
Background: The practice of appropriate health care-seeking is important to reduce severe and life-threatening childhood illnesses. In Shire town, little is known about the mother's health care-seeking behaviour on childhood illness. Aim: To assess modern health-seeking behaviour and associated factors of mothers having under 5-years old children in Shire town. Setting: The study setting was Shire town, northwest Tigray, Ethiopia. Methods: A community-based cross-sectional study was conducted to interview 504 mother-child pairs by systematic random sampling technique. Data were collected through interviewer-administered semi-structured questionnaires. Data were coded, entered, cleaned and edited using EPIDATA version 3.1 and export to Statistical Package for Social Science (SPSS) Version 22.0 for analysis. To identify the significant variables, binary logistic regression was employed. Variables with p-value 0.05 at 95% CI (confidence interval) in multivariate logistic regression were considered statistically significant. Results: In this study, around 76.2% (72.1, 80) of mothers sought modern health care. In a multivariate logistic regression analysis at a p-value of 0.05, caregivers with age of ≥ 28 years (AOR [adjusted odds ratios]: 1.65; 95% CI [1.02, 2.68]), educational level of secondary school and above (AOR: 0.44; 95% CI [0.23, 0.86]), child feeding per day 8 times (AOR: 2.77; 95% CI [1.75, 4.38]) and perceived severity of illness (AOR: 2; 95% CI [1.07, 3.82]) were statistically associated with modern health care-seeking behaviour. Conclusion: Strengthen healthcare services is recommended at the community level through information, education and communication/behavioural change strategies to improve the mother's health care-seeking behaviour.